Effect of Organizational Climate and Achievement Motivation on Teacher Performance - Mustika Adriana; Didik Santoso; Yusuf Hadijaya; Fuad Srinio (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine how big the significant influence of organizational climate and achievement motivation on teacher performance at SMKN 1 Percut Sei Tuan. This research is quantitative research with the type of Causal Comparative Research (ex post facto). The population is the teachers of SMKN 1 Percut Sei Tuan which is the sample in this study consisting of 88 teachers. This research instrument uses a data questionnaire on organizational climate, achievement motivation, and teacher performance. Data analysis was carried out using path analysis. Organizational climate has a significant influence on teacher performance at SMKN Percut Sei Tuan by 87.6%, the better the organizational climate, the higher the teacher's performance. Achievement motivation has a significant influence on teacher performance at SMKN 1 Percut Sei Tuan by 89.2%, the higher the achievement motivation, the higher the teacher's performance. Organizational climate and achievement motivation simultaneously (together) have a significant effect on teacher performance at SMKN 1 Percut Sei Tuan by 90.9%, the better the organizational climate and the higher the achievement motivation, the higher the teacher's performance.